Dampak Pemanfaatan Elektronik Rekam Medis di Fasilitas Kesehatan: Pendekatan Sistematik Literatur Review - Arsyam, Haeril; Sulaiman, Lalu; Setiawan, Sabar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study examines the impact of Electronic Medical Records (ERM) implementation in healthcare facilities over the last decade, focusing on its benefits and challenges. ERM has significantly improved patient care quality, operational efficiency, and data security, providing fast and accurate access to medical information for clinical decision-making. However, despite these advantages, the adoption of ERM faces several technical and organizational challenges, including limited interoperability between systems and user resistance. A systematic literature review was conducted, analyzing studies from 2014-2024, to explore both the positive outcomes and barriers encountered during ERM implementation. The results indicate that while ERM reduces medical errors and enhances care coordination, particularly in managing chronic conditions, issues such as data privacy concerns and high implementation costs remain significant barriers. Recommendations to address these challenges include the development of standardized policies for system interoperability and comprehensive user training to facilitate adaptation. This study underscores the need for a more integrated approach that combines technical improvements with organizational support to maximize the potential benefits of ERM.